Social Media as An Incubator of Youth Terrorism In Indonesia: Hybrid Threat and Warfare - Achmad Zainal Huda; A. Josias Simon Runturambi; Muhammad Syauqillah (JURNAL INDO-ISLAMIKA, 2021)
The presence of technology, such as social media in cyberspace brings its own benefits to the terrorist groups. Terrorist groups use social media to recruit, influence, rally and invite as many people as possible to join them. Adolescent has become terrorist groups’ new target for their regeneration. The characteristics of adolescents who are looking for self-value and having an interest towards social media, makes them vulnerable to be targeted by terrorist groups. This research is a qualitative research with a case study method of four teenagers’ terrorists. This study aims to analyze how social media acts as an incubator of terrorism among Indonesian teenagers and to analyze how this phenomenon can be categorized as part of Hybrid warfare. The analytical techniques in this study are documentation studies from the news that spread across social media. This research shows that terrorist groups through social media provide anxiety narratives, and provide a role for teenagers to contribute through the path of jihad. To overcome this, the Indonesia government needs to place cyber terrorism in the framework of Hybrid warfare so that the weaponry components and strategies used can be holistic and multidimensional.